How Does Word of Mouth Mediate the Relationship between Lifestyle and Product Quality to Customer Loyalty? - Saputra, Wahyu Dwi; Santosa, Perdana Wahyu (Marketing and Business Strategy, 2024)
This study examines the influence of lifestyle and product quality on customer loyalty, with word of mouth (WoM) as a mediating factor for Erigo products. The research focuses on YARSI University students (Batch 2016-2019) who have purchased Erigo products. It contributes to consumer behavior and marketing literature by highlighting WoM's role in fostering loyalty to local fashion brands. The sample consists of 100 respondents who purchased Erigo products 1-2 times, 3-4 times, or more than 4 times, selected through purposive sampling with a non-probability method. Data were collected via questionnaires and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). Findings reveal that lifestyle and product quality significantly influence WoM. Lifestyle directly impacts customer loyalty, while product quality does not. WoM strongly affects customer loyalty and mediates the relationship between both lifestyle and product quality with loyalty. These results emphasize WoM's critical role in enhancing loyalty, reinforcing the importance of targeting lifestyle alignment and product quality in Erigo’s marketing strategies. By leveraging WoM effectively, Erigo can strengthen customer retention and advocacy among its student consumer base.